Angulation change of the third molar tooth in orthodontic treatment - Ardiansyah S. Pawinru (DiscoverSys Inc., 2017)
Objective : Impaction of the third molar tooth mandibular is often found in patients with orthodontic treatment. In orthodontic treatment, extraction cases of impaction of the third molar tooth are usually performed, but the patients often refuse this extraction. Extraction of premolar has a good effect on the third molar mandibular angulation during treatment.Material and Methods : This study is a retrospective clinical study with descriptive analytic to find out the effect of the first mandibular premolar tooth extraction to angulation change of the third molar mandibular in orthodontic treatment with a standard edgewise method. Angulation change was performed by comparing the third molar mandibular angulation before and after orthodontic treatment with panoramic radiographs. Angulation of the third molar tooth mandibular was calculated from the angle formed between the long axis of the tooth with the reference line infraorbita.Results : The sample comprised 60 of impacted mandibular third molar region of the left and right regions of 30 patients who had been treated declared cured in clinic of orthodontic specialist of Dentistry Faculty Padjadjaran University. The sample was divided into three (3) groups of patients before treatment angulation of the third molar tooth mandibular under 300, 300 to 600 and above 60o, then measured change of angulation and observed whether it increased, fixed or decreased. Results were analyzed by T- test and Wilcoxon test showed that there was a significant change in angulation of the third molar mandibular in orthodontic treatment with the first premolar tooth mandibular extraction.Conclusion : This study is that the first premolar tooth mandibular extraction affects the angulation of the third molar tooth mandibular after orthodontic treatment.